A comparative phase 1 clinical trial to identify anti-infective mechanisms of vitamin D in people with HIV infection. (19th June 2015) - Lachmann, Raskit; Bevan, Margaret A.; Kim, Sangmi; Patel, Nishma; Hawrylowicz, Catherine; Vyakarnam, Annapurna; Peters, Barry S.
Abstract : Objectives: To determine if there is a biological mechanism that explains the association between HIV disease progression and increased mortality with low circulating vitamin D levels; specifically, to determine if restoring vitamin D levels induced T-cell functional changes important for antiviral immunity. Design: This was a pilot, open-label, three-arm prospective phase 1 study. Methods: We recruited 28 patients with low plasma vitamin D (<50 nmol/l 25-hydroxyvitamin D3), comprising 17 HIV+ patients (11 on HAART, six treatment-naive) and 11 healthy controls, who received a single dose of 200 000 IU oral cholecalciferol. Advanced T-cell flow cytometry methods measured CD4 + T-cell function associated with viral control in blood samples at baseline and 1-month after vitamin D supplementation. Results: One month of vitamin D supplementation restored plasma levels to sufficiency (>75 nmol/l) in 27 of 28 patients, with no safety issues. The most striking change was in HIV+ HAART+ patients, where increased frequencies of antigen-specific T cells expressing macrophage inflammatory protein (MIP)-1β – an important anti-HIV blocking chemokine – were observed, with a concomitant increase in plasma MIP-1β, both of which correlated significantly with vitamin D levels. In addition, plasma cathelicidin – a vitamin D response gene with broad antimicrobial activity – was enhanced. Conclusion: Vitamin D supplementation modulates disease-relevant T-cell functions in HIV-infected patients, and may represent a useful adjunct to HAART therapy. Abstract : Supplemental Digital Content is available in the text